Líquidos iônicos dicatiônicos: propriedades físicoquímicas e interações com fármacos - Bender, Caroline Raquel (2018)
This study presents the influence of the molecular structure of dicationic ionic liquids (ILs) derived from imidazolium ring, on physicochemical properties, self-association and heteroassociation. Changes in solubility properties, diffusion coefficient, relaxation time and decomposition kinetics were evaluated as a function of the anion structure, for the ILs of 1,8-bis (3-methylimidazol-1-yl) octane cation ([BisOct(MIM)2]2+). The results showed that the partition constant decreases according to the anion in the following order: [BF4]- > [SCN]- > [NO3]- > [Br]- > [Cl]-. Thermal stability is also associated with the anion, in which [BisOct(MIM)2][2NO3] is the most stable IL. On the other hand, the diffusion coefficient data did not vary according to the anion under the conditions tested. The kinetics of the decomposition of dicationic ILs ([BisAlq(MIM)2][2Br]) with different alkyl chain length (10, 12 and 14 carbons) was also evaluated and compared with monocationic analogues. It has been found that the stability is not related with the number of carbons in the structure and that the dicationic IL are more stable than monocationic analogs. The organization and morphology of aggregates of dicationic ILs [BisOct(MIM)2][2X], in which X = Br, NO3, BF4 and SCN, were investigated. It has been observed that the cation alkyl spacer chain is folded, forming spherical aggregates and, that interactions occurring on the aggregate’s surface are dependent on the anions type. Thermodynamic parameters of the aggregation process (ΔG°a, ΔH°a and TΔS°a) determined for [BisOct(MIM)2][2Br] showed that the process is enthalpy driven. In addition, it has been observed that as the temperature increases, the free energy of aggregation (ΔG°a) decreases and the free energy of adsorption increases (ΔG°ads) indicating that the aggregation hability decreases and the IL adsorption at the liquid/air interface increases. In the study of heteroassociation, it was investigated heteroassociation of dicationic ILs with different active pharmaceutical ingredients (APIs): salicylic acid (AS), ibuprofen (Ibu) and Paracetamol (Par). It was observed that ILs and IFAs interact at low concentrations (~2 mM) in ethanol-water solution (1:1, v/v). At high concentrations (~50 mM), the APIs were found to interact probably at aggregates surface of the ILs. Interactions between ILs and APIs have also been proven with both components in the solid state. The supramolecular structure of the system [BisOct(MIM)2][2Br] + AS was obtained by monocrystal X-ray diffraction.